2017
DOI: 10.1007/s10103-017-2237-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of photobiomodulation therapy and suprascapular nerve-pulsed radiofrequency in chronic shoulder pain: a randomized controlled, single-blind, clinical trial

Abstract: Shoulder pain can be difficult to treat due to its complex anatomic structure, and different treatment methods can be used. We aimed to examine the efficacy of photobiomodulation therapy (PBMT) and suprascapular nerve (SSN)-pulsed radiofrequency (RF) therapy. In this prospective, randomized, controlled, single-blind study, 59 patients with chronic shoulder pain due to impingement syndrome received PBMT (group H) or SSN-pulsed RF therapy (group P) in addition to exercise therapy for 14 sessions over 2 weeks. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…P-RF was statistically superior to intra-articular steroid injection [3], physical therapy alone [6], and lidocaine only [8] nerve block for a maximum duration of 12 weeks or 3 months. However, p-RF was not significantly superior to transcutaneous electrical nerve stimulation at 12 weeks [4], lidocaine only nerve block at 6 months [5], or photobiomodulation therapy at 6 months [7]. There were no RCTs found that assessed the efficacy of PNS therapy to the suprascapular nerve in chronic refractory shoulder pain patients.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…P-RF was statistically superior to intra-articular steroid injection [3], physical therapy alone [6], and lidocaine only [8] nerve block for a maximum duration of 12 weeks or 3 months. However, p-RF was not significantly superior to transcutaneous electrical nerve stimulation at 12 weeks [4], lidocaine only nerve block at 6 months [5], or photobiomodulation therapy at 6 months [7]. There were no RCTs found that assessed the efficacy of PNS therapy to the suprascapular nerve in chronic refractory shoulder pain patients.…”
Section: Literature Reviewmentioning
confidence: 96%
“…After searching Medline and Google Scholar databases, six randomized controlled trials (RCT) on p-RF therapy involving the suprascapular nerve were found and are summarized in Table 3 [3][4][5][6][7][8]. Most patients in these studies noted improvement in pain, disability scores, and shoulder joint range of motion from their baseline to post p-RF therapy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Full texts of the remaining 90 articles were assessed for eligibility and, of these, 42 studies with data on 1,018 patients and published between 1988 and 2019 fulfilled our inclusion criteria (Tables 1 and 2). These included eight comparative studies-seven of these were randomized control trials (RCT) (Eyigor et al, 2010;Gofeld et al, 2013;Korkmaz et al, 2010;Okmen & Okmen, 2017;M. Taverner & Loughnan, 2014;Wu et al, 2014;Yan & Zhang, 2019) and one was a retrospective study in which pRF and injection of LA on the SSN were offered to both the groups with steroids being injected in one group (Gabrhelik et al, 2010) (Table 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…A 22-gage, 100 mm, 5 mm active-tip radiofrequency needle was guided to the suprascapular notch under ultrasonography (linear transducer with a scanning frequency of 12 MHz). 22 Anatomic landmarks were used for transducer position (the spine of the scapula, the acromion and the acromial end of the clavicle, and the coracoid process) and SSN localization (the trapezius muscle, the supraspinatus muscle, the supraspinous fossa, and the suprascapular and the spinoglenoid notch). The SSN was identified as a hyperechoic structure 3–4 cm deep and below the transverse scapular ligament in the scapular notch.…”
Section: Methodsmentioning
confidence: 99%
“… 23 Following elicitation of paresthesia response in the shoulder region to a 50 Hz, 1 ms, 0.5 V sensorial stimulus and appropriate muscular response to a 2 Hz, 1 ms, 0.4 V motor stimulus, PRF treatment was applied at 485 kHz, 42 V, 20 ms, 42°C for 300 s (5 min; TherMedico NK1; schwa-medico GmbH, Ehringshausen, Germany). 22 , 23 Patients were discharged if no significant complications occurred (eg, pain, bleeding, or pneumothorax).…”
Section: Methodsmentioning
confidence: 99%